2021
DOI: 10.3389/fbioe.2021.703508
|View full text |Cite
|
Sign up to set email alerts
|

Using Musculoskeletal Models to Estimate in vivo Total Knee Replacement Kinematics and Loads: Effect of Differences Between Models

Abstract: Total knee replacement (TKR) is one of the most performed orthopedic surgeries to treat knee joint diseases in the elderly population. Although the survivorship of knee implants may extend beyond two decades, the poor outcome rate remains considerable. A recent computational approach used to better understand failure modes and improve TKR outcomes is based on the combination of musculoskeletal (MSK) and finite element models. This combined multiscale modeling approach is a promising strategy in the field of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Finite element studies of knee protheses suggest that musculoskeletal models would affect the knee joint's kinematic and kinetic outcomes. 101 Shu et al proposed an FEM verified by in vivo fluoroscopy, pressure sensors, and EMG for preoperative testing of a newly invented knee prosthesis. 59 Fernando et al suggested that reducing the tibial prosthesis size could prevent excessive prosthesis internal rotation.…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Finite element studies of knee protheses suggest that musculoskeletal models would affect the knee joint's kinematic and kinetic outcomes. 101 Shu et al proposed an FEM verified by in vivo fluoroscopy, pressure sensors, and EMG for preoperative testing of a newly invented knee prosthesis. 59 Fernando et al suggested that reducing the tibial prosthesis size could prevent excessive prosthesis internal rotation.…”
Section: Osteoarthritismentioning
confidence: 99%
“…Further, finite element analysis can assist in designing and selecting knee prosthesis, guiding surgeons to optimize the operation in time. Finite element studies of knee protheses suggest that musculoskeletal models would affect the knee joint's kinematic and kinetic outcomes 101 . Shu et al .…”
Section: Application and Characteristicsmentioning
confidence: 99%
“…Tunable parameters are i) the bone inertial properties, ii) the skeletal morphologies, iii) the muscle architectures; all these features could allow for an improved inter-subject, healthy/impaired muscle activation evaluation in the future 21 . However, subject-specific models require complex modeling workflows 24,25 and well-defined methods, especially for musculotendon parameters estimation. For our study, given the nature of the recorded kinematics (all subjects using the same exoskeleton) and the collected information about the subjects (see following section), a fixed scaling was applied to match a generic model to all subjects, so that all subjects would have a common basis for the model outputs evaluations, based on their movement and their EMG recorded 26 .…”
Section: Numerical Modelmentioning
confidence: 99%
“…However, this approach is costly, invasive, and not feasible in large cohorts. Thus, musculoskeletal (MSK) model-based simulations based on 3D motion capture (MoCap) data represent the state-of-the-art method to estimate in-vivo joint loading [24], [25]. Several groups have reported good agreement between MSK model-based and instrumented knee implant joint loading parameters [26], [27], hence making it a feasible alternative to instrumented prosthesis [26], [28] with the advantage of being able to be applied to larger clinicial cohorts.…”
Section: Introductionmentioning
confidence: 99%